THE USE OF GEOGRAPHIC INFORMATION SYSTEMS (GIS) IN VETERINARY MEDICINE - Suyunova, Seytvelieva Sevilya; Daminov, Asadullo Suvonovich (Educational Research in Universal Sciences, 2023)
This article is devoted to an overview of the possibilities and potential use of the Geographic Information System (GIS) in the field of veterinary surveillance and monitoring of natural focal zooanthroponotic cestodosis.